Protostars and planets VI - Beuther, Henrik; Klessen, Ralf S.; Dullemond, Cornelis; Henning, Thomas (University of Arizona Press, 2014)
Intro -- Contents -- Scientific Advisory Committee and List of Collaborating Authors -- Preface -- Part I: Molecular Clouds and Star Formation -- Formation of Molecular Clouds and Global Conditions for Star Formation / C. L. Dobbs, M. R. Krumholz, J. Ballesteros-Paredes, A. D. Bolatto, Y. Fukui, M. Heyer, M.-M. Mac Low, E. C. Ostriker, and E. Vázquez-Semadeni -- From Filamentary Networks to Dense Cores in Molecular Clouds: Toward a New Paradigm for Star Formation / P. André, J. Di Francesco, D. Ward-Thompson, S.-I. Inutsuka, R. E. Pudritz, and J. Pineda -- The Origin and Universality of the Stellar Initial Mass Function / S. S. R. Offner, P. C. Clark, P. Hennebelle, N. Bastian, M. R. Bate, P. F. Hopkins, E. Moreaux, and A. P. Whitworth -- The Star Formation Rate of Molecular Clouds / P. Padoan, C. Federrath, G. Chabrier, N. J. Evans II, D. Johnstone, J. K. Jørgensen, C. F. McKee, and Å. Nordlund -- The Link Between Magnetic Fields and Cloud/Star Formation / H.-B. Li, A. Goodman, T. K. Sridharan, M. Houde, Z.-Y. Li, G. Novak, and K. S. Tang -- The Milky Way as a Star Formation Engine / S. Molinari, J. Bally, S. Glover, T. Moore, A. Noriega-Crespo, R. Plume, L. Testi, E. Vázquez-Semadeni, A. Zavagno, J.-P. Bernard, and P. Martin -- Massive Star Formation / J. C. Tan, M. T. Beltrán, P. Caselli, F. Fontani, A. Fuente, M. R. Krumholz, C. F. McKee, and A. Stolte -- The Earliest Stages of Star and Planet Formation: Core Collapse, and the Formation of Disks and Outflows / Z.-Y. Li, R. Banerjee, R. E. Pudritz, J. K. Jørgensen, H. Shang, R. Krasnopolsky, and A. Maury -- The Evolution of Protostars: Insights from Ten Years of Infrared Surveys with Spitzer and Herschel / M. M. Dunham, A. M. Stutz, L. E. Allen, N. J. Evans II, W. J. Fischer, S. T. Megeath,P. C. Myers, S. S. R. Offner, C. A. Poteet, J. J. Tobin, and E. I. Vorobyov.
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2013 -- Heidelberg; Planet; Protostern; Sternentstehung